Biotransformation of the residual hair from the tannery industry - Numpaque P., Ruth Viviana; Viteri R., Silvio Edgar (Revista de Ciencias Agrícolas, 2016)
The tannering industry generates effluent with high contaminant load represented in a considerable amount of liquid, solid and gaseous waste. Among the solid wastes, the residual hair is dumped directly to the Bogota River or in landfills, triggering serious environmental, social and economic conflicts. The objective of this research was to evaluate the capacity of the EM and Agroplux microorganisms to transform the residual animal hair into compost. Three treatments, with different percentages of residual hair and urban organic residues and two controls, were evaluated, using a completely randomized experimental design, with three replications. During the composting process the variables temperature, aggregate formation, electrical conductivity and pH were evaluated. The development of temperature displayed cycles which were in accordance with the over turnings and re-inoculations of the compost piles. In the third cycle the greater increment in temperature was obtained in the three treatments, when the majority of the organic residues were almost completely decomposed. The aggregate formation indicated that the composting process took place principally in the treatment with 20% of residual hair and 80% of solid organic residues. In addition to the dark color and the absence of odor and of fragments of the original materials, the compost produced by means of this treatment showed the lower electrical conductivity and a pH almost reached to be neutral. It is concluded that the EM and Agroplux microorganisms have capacity to transform the residual hair into compost, and in consequence, they represent a viable alternative which can be adopted by the tannery industry to continue operating in Villapinzón (Cundinamarca) and in other regions of the country.